Sprache in Wissenschaft und Dichtung. Diskursive Formationen von Mathematik, Physik, Logik und Dichtung im 17. und 18. Jahrhundert - Illi, Manuel (Literatur- und Naturwissenschaften, 2017)
In the 17th and 18th centuries, language and linguistic reflections were a central determinant of the discursive relationship between mathematics, physics, logic, and literature. The volume traces these constellations, examining linguistic, technical, and poetological texts to reveal the close connections between the language of literature, poetology, and scientific discourse.